Hostile takeovers and methods of defense: A stakeholder analysis - Hanly, Ken (Journal of business ethics, 1992)
During the last decade, there has been a wave of mergers and hostile takeovers throughout the corporate world. This wave has been accompanied by various defensive strategies of managers to defend target firms from these takeovers. These include: greenmail, golden parachutes, and leveraged management buyouts. This paper examines hostile takeovers and defenses against them from a stakeholder point of view; that is, from a consideration of the various obligations a firm has to the different groups that have a stake in the firm. I conclude that many stakeholders, such as workers and communities, have unjustly suffered as a result of hostile takeovers and the associated defenses, and that their rights as stakeholders have been violated. Finally, I suggest some possible reforms to protect these stakeholders in the future.